Medical Computer Vision: Recognition Techniques and Applications in Medical Imaging Second International MICCAI Workshop, MCV 2012, Nice, France, October 5, 2012, Revised Selected Papers - Menze, Bjoern; Langs, Georg; Lu, Le; Montillo, Albert; Tu, Zhuowen; Criminisi, Antonio (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2013)
This book constitutes the thoroughly refereed workshop proceedings of the Second International Workshop on Medical Computer Vision, MCV 2012, held in Nice, France, October 2012 in conjunction with the 15th International Conference on Medical Image Computing and Computer Assisted Intervention, MICCAI 2012. The 24 papers have been selected out of 42 submissions. At MCV 2012, 12 papers were presented as a poster and 12 as a poster together with a plenary talk. The book also features four selected papers which were presented at the previous CVPR Medical Computer Vision workshop held in conjunction with the International Conference on Computer Vision and Pattern Recognition on June 21 2012 in Providence, Rhode Island, USA. The papers explore the use of modern computer vision technology in tasks such as automatic segmentation and registration, localization of anatomical features and detection of anomalies, as well as 3D reconstruction and biophysical model personalization.